2014
DOI: 10.1007/s11274-014-1678-0
|View full text |Cite
|
Sign up to set email alerts
|

Separation and purification of bioactive botrallin and TMC-264 by a combination of HSCCC and semi-preparative HPLC from endophytic fungus Hyalodendriella sp. Ponipodef12

Abstract: Two dibenzo-α-pyrones, botrallin (1) and TMC-264 (2) were preparatively separated from crude ethyl acetate extract of the endophytic fungus Hyalodendriella sp. Ponipodef12, which was isolated from the hybrid 'Neva' of Populus deltoides Marsh × P. nigra L. using a combination of high-speed counter-current chromatography (HSCCC) and semi-preparative HPLC. Botrallin (1) with 74.73% of purity and TMC-264 (2) with 82.29% of purity were obtained through HSCCC by employing a solvent system containing n-hexane-ethyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Ponipodef12 was isolated as an endophytic fungus from the hybrid poplar of Populus deltoides × P. nigra [9]. This endophytic fungus was known to produce benzo-α-pyrones, dibenzo-α-pyrones [10][11][12][13] and 14-membered resorcylic acid lactones [14], and in our previous investigations, among them dibenzo-α-pyrones showed larvicidal activities [10]. Nevertheless, Hyalodendriella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Ponipodef12 was isolated as an endophytic fungus from the hybrid poplar of Populus deltoides × P. nigra [9]. This endophytic fungus was known to produce benzo-α-pyrones, dibenzo-α-pyrones [10][11][12][13] and 14-membered resorcylic acid lactones [14], and in our previous investigations, among them dibenzo-α-pyrones showed larvicidal activities [10]. Nevertheless, Hyalodendriella sp.…”
Section: Introductionmentioning
confidence: 99%
“…[22] [23] Considering the advantages of macroporous resin columns and semipreparative RPLC, these two techniques were combined in this study to isolate the target compound. However, efficient preparative separation and purification methods for natural compounds are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-preparative reversed-phase liquid chromatography (semi-preparative RPLC) is gradually becoming a powerful tool by virtue of its high efficiency and resolution. [22] [23] Considering the advantages of macroporous resin columns and semipreparative RPLC, these two techniques were combined in this study to isolate the target compound. Macroporous resin columns were mainly used to enrich the effective fraction and semi-preparative RPLC was used to separate the target compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In such a situation, preparative HPLC (prep‐HPLC), an extensively used classical separation technique is a good complement for HSCCC . Previous studies have demonstrated the effectiveness of HSCCC combined with prep‐HPLC for separating monomeric compounds from complex samples, thus significantly saving elution time and a large amount of solvents . Therefore, high purity compounds could be separated from S. chusanum Ching by using HSCCC coupled to prep‐HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated F I G U R E 1 Chemical structures of the separated compounds 1-7. 3,4-Dihydroxy benzoic acid (1), 3,4-dihydroxy benzaldehyde (2), esculetin (3), caffeic acid (4), syringic acid (5), luteolin (6), and apigenin (7) the effectiveness of HSCCC combined with prep-HPLC for separating monomeric compounds from complex samples, thus significantly saving elution time and a large amount of solvents [17,18]. Therefore, high purity compounds could be separated from S. chusanum Ching by using HSCCC coupled to prep-HPLC.…”
Section: Introductionmentioning
confidence: 99%